Slang Words Used by the Millennial Indonesian Generation in TikTok - Manihuruk, Leo Lihardo; Ginting, Desinta; Manik, Sondang; Manurung, Lastri W (English Lecturers and Teachers Association (ELTA), 2025)
Language is used in various ways, especially among the younger generation. The millennial generation, in particular, exhibited a higher tendency to use slang in daily conversations rather than formal language. This study aimed to analyze the phenomenon of slang words used by the millennial generation on TikTok. The research investigated the types of slang employed by millennials on TikTok and explored the meanings of these slang words. A descriptive qualitative approach was applied, and data were obtained through observation. The analyzed data consisted of videos and comments collected from TikTok users (@adridilapangasebagaipap and @slametnovendraa) between January 12 and January 19, 2024. The findings revealed that 435 slang words were used during the observed period. These words fell into three types of slang: imitative, acronyms, and clipping. Additionally, four frequently used slang words were identified: